ZWIĄZEK PRZYCZYNOWY JAKO PRZESŁANKA ODPOWIEDZIALNOŚCI SPÓŁKI PUBLICZNEJ ZA NARUSZENIE OBOWIĄZKÓW INFORMACYJNYCH - Sójka, Tomasz (Wydział Prawa i Administracji UAM, 2007)
The paper analyzes the problem of causation in cases for damages connected with false or misleading statements in the reports o f public corporations - in this context causation is not only a condition for a responsibility but also a factor influencing the amount of damages. The scope of the paper is limited to the reporting requirements o f issuers o f shares in the part of capital market defined as “the regulated market”; the reporting requirements encapsulate here not only the continuous disclosure obligations of public corporations but also a duty to publish a prospectus in connection with an issuance of shares. The aim o f the paper was to answer two questions: (1) under which conditions can the court establish “a normal causation relationship” between a false or misleading statement in the report and the mistaken investment decision of the market participant; (2) which losses incurred by an investor result from normal consequences o f a mistaken investment decision made on the basis of a false or misleading statement.
CAUSATION AS A LEGAL RESPONSIBILITY OF A PUBLIC CORPORATION FOR INFRINGEMENT OF DISCLOSURE OBLIGATIONS